Integrating Deep Learning and Hypnoteaching to Improve Oral Communication Skills: A Research of Dental Nursing Students at Poltekkes Kemenkes Makassar - Basir, Achmad (English Language Teaching Methodology, 2025)
This research aimed to investigate the effectiveness of integrating Deep Learning and Hypnoteaching in improving the oral communication skills of dental nursing students at Poltekkes Kemenkes Makassar. The significance of this research is based on the importance of oral communication competence in health education, while many students experience anxiety and low self-confidence, especially in the context of multicultural interaction. The novelty of this research lies in the implementation of a holistic learning approach that combines technology-based Deep Learning features with the psychological technique of Hypnoteaching to simultaneously address cognitive and emotional aspects of communication. The method used is a quantitative approach with a one-group pretest–posttest pre-experimental design involving 40 Dental Nursing students of Class 2A Diploma IV in the 2025 Academic Year, during six intervention sessions with an assessment of oral communication skills using a structured performance rubric. The findings revealed a statistically significant improvement in students’ oral communication performance, with the mean score increasing from 15.9 in the pretest to 22.2 in the posttest, representing a 39.6% improvement, particularly in self-confidence, pronunciation clarity, and response accuracy. Qualitative feedback further indicated reduced anxiety, increased motivation, and improved focus during speaking tasks. The results of research contribute to providing an innovative learning model based on the integration of technology and an effective psychological approach, and concludes that the application of Deep Learning and Hypnoteaching is proven to be able to improve the quality of oral communication of dental nursing students.